If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 4b + 4 = 7b + -5 Reorder the terms: 4 + 4b = 7b + -5 Reorder the terms: 4 + 4b = -5 + 7b Solving 4 + 4b = -5 + 7b Solving for variable 'b'. Move all terms containing b to the left, all other terms to the right. Add '-7b' to each side of the equation. 4 + 4b + -7b = -5 + 7b + -7b Combine like terms: 4b + -7b = -3b 4 + -3b = -5 + 7b + -7b Combine like terms: 7b + -7b = 0 4 + -3b = -5 + 0 4 + -3b = -5 Add '-4' to each side of the equation. 4 + -4 + -3b = -5 + -4 Combine like terms: 4 + -4 = 0 0 + -3b = -5 + -4 -3b = -5 + -4 Combine like terms: -5 + -4 = -9 -3b = -9 Divide each side by '-3'. b = 3 Simplifying b = 3
| 8(x-7)=x(x-7) | | (10x-4)(3x+2)=0 | | 3a+1=5a-3 | | 4z+2=10z-1 | | c-1=2c-8 | | b+3=3b+1 | | 10a+1=8a+9 | | 3c-2=2c+4 | | -x^2+3x-1=0 | | (5-2x)+(4x-13)=2 | | 2b-7=b-3 | | x-3+9(8-6)= | | 3a+1=a+7 | | 5.6+1.6= | | 35-5x=4x+20 | | 4x+7=-48-7x | | 176-7x=20x+23 | | (3z+8)(5+z)=0 | | 10-8x=33-15x | | 12x+11=-109-7x | | 6b-3=-9 | | 12y-(y+5)=10y-1 | | 5x^2-10x-3.14=0 | | Y=2x^3-x+8 | | 8x+14=4x+94 | | 49-2x=7x+12 | | 9-8x=99-43x | | 5-x=4x+40 | | 8x-4=5x+32 | | 5x-7=-27 | | 5x+7=28-2x | | 7x=3x+32 |